PENGEMBANGAN APLIKASI PENGELOLA TUGAS KARYAWAN DENGAN METODE ISDM BERBASIS WEB MOBILE - Hakim, Faishal; Hidayat, Ahmad Tri (Program Studi Informatika Universitas Teknologi Sumbawa, 2024)
This study addresses the challenges of task management at Maju Makmur Utomo, focusing on the need for more efficient monitoring and reporting of employee performance. A web-based application for managers and a mobile application for employees were developed using React.js, React Native, Express.js, and MongoDB to streamline overall task management processes. The method used was the Initial Software Development Method (ISDM), which provides a structured framework for a single developer to manage the software development lifecycle. Data was collected through interviews, observations, and related literature reviews, providing in-depth insights into user needs and preferences. The key findings of this study show that the implementation of this information technology-based application significantly improved task tracking efficiency, employee engagement, and company productivity. Additionally, this solution provided better task management. This research highlights the importance of applying modern technology to resolve task management challenges within organizations, particularly in business environments like Maju Makmur Utomo.